An Innovative Model of Problem-Based Learning: Exploring Interactional Attitudes as a Pedagogical Innovation in a Novel Context with Emphasis on Character-Based Learning - Karlin Geriun Antonius Manik; Verawaty Sinaga; Yubena Abigail Serewati Tambunan; Isyeu Nur Cahyani (Journal of Innovation in Educational and Cultural Research, 2025)
Character development in students is an essential aspect of education, complementing efforts to enhance cognitive abilities and skills. Effective teaching strategies play a crucial role in fostering character growth, and Problem-Based Learning (PBL) has emerged as a promising pedagogical approach in this regard. This study aims to analyze the differences in character development between students engaged in PBL and those taught through direct instruction (traditional teaching methods). A literature review methodology was employed, synthesizing previous research on the integration of character development within PBL-based learning models. Student character was assessed using character observation sheets during laboratory sessions. The findings reveal that while teaching strategies do not exert a statistically significant influence on character development, students exposed to PBL demonstrated greater improvements in character attributes compared to those taught through traditional instruction. These results suggest that PBL should be considered a preferred teaching approach to cultivate students' character alongside their academic competencies. The study highlights the need for more precise measurement tools, such as behavioral observation sheets, to better assess character development. This research contributes to the advancement of educational methodologies, offering insights for educators and policymakers on the potential of PBL in shaping well-rounded individuals.